Coordinated views to assist exploration of spatio-temporal data: a case study - Shimabukuro, M. H.; Flores, E. F.; de Oliveira, MCF; Levkowitz, H. (Institute of Electrical and Electronics Engineers (IEEE), Computer Soc, 2004)
In this paper we focus on providing coordinated visual strategies to assist users in performing tasks driven by the presence of temporal and spatial attributes. We introduce temporal visualization techniques targeted at such tasks, and illustrate their use with an application involving a climate classification process. The climate classification requires extensive Processing of a database containing daily rain precipitation values collected along over fifty years at several spatial locations in the São Paulo state, Brazil. We identify user exploration tasks typically conducted as part of the data preparation required in this process, and then describe how such tasks may be assisted by the multiple visual techniques provided. Issues related to the use of the multiple techniques by an end-user are also discussed.
Keywords: temporal visualization techniques; multiview visualization; visual data analysis